Evaluation of Changes in the Expression Profile of mRNA and Proteinencoding Adiponectin in Ishikawa Cell Line under the Influence of Cisplatin – Preliminary Report - Kiełabsiński, Robert; Kieszkowski, Przemysław; Grabarek, Beniamin O.; Boroń, Dariusz (Current Pharmaceutical Biotechnology, 2020)
Background: A reduced concentration of adiponectin is considered as an independent factor of the risk of inducing endometrial cancer. Cisplatin is a drug used in the therapy of this type of neoplasm. However, knowledge of the effects of cisplatin on the adiponectin level is still limited. Objective: The purpose of this study was to assess the impact of cisplatin depending on the concentration and time of exposition of the cells to the drug on the adiponectin level in the endometrial cancer cell line. Methods: Cells of endometrial cancer cell line Ishikawa were exposed for 12,24 and 48 hour periods to cisplatin with the following concentrations: 2.5μM, 5μM, 10μM. The changes in the expression profile of adiponectin were compared to the RtqPCR reaction and ELISA test. The STATISTICA 13.0 PL program was used for statistical analysis (p<0.05). Results: In the culture without the drug, the concentration of adiponectin was statistically lower than in the cell culture incubated with the drug. Changes on the mRNA level seem to be more specific than on the protein level, although in both cases, the same trend in the expression changes was noted. Discussion: The longer the time of exposition of the cells to the drug, the expression of mRNA, and the adiponectin protein increased. Changes in the expression profile were characterized statistically (p<0.05). Conclusion: Cisplatin, in a noticeable way, changes the expression profile of adiponectin. Molecular analysis indicated that in the case of endometrial cancer therapy should be implemented with a concentration of no less than 5 μM.
Keywords: Adiponectin